Adaptive fuzzy sliding mode based MPPT controller for a photovoltaic water pumping system - Sabah Miqoi; Abdelghani El Ougli; Belkassem Tidhaf (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The applications of photovoltaic energy are steadily increasing. However, the output power of a photovoltaic system is influenced by the meteorological conditions (temperature and irradiation), which can affect the production and efficiency of the photovoltaic panel energy. So to ensure that the photovoltaic panel produces its maximum power possible at any time and regardless of the external conditions, we use the equipment called MPPT (maximum power point tracker). Sliding mode control is recognized by its stability and robustness and widely used in non-linear systems but represents a disadvantage because of the chattering phenomena. So in order to overcome this problem and improve this control, we opted to add to it the adaptive fuzzy control which will adapt the switching gain. This controller is named AFSMC (adaptive fuzzy sliding mode control) and will be compared the sliding mode controller SMC in order to see the difference and to the P&O (perturb & observe) method to validate this controller. Our system consists of a photovoltaic panel a DC-DC boost converter and a centrifugal pump with a DC motor. All simulations are carried out under MATLAB/SIMULINK and the extracted results show the efficiency of the AFSMC controller and confirm that the new methods have improved energy efficiency and production